Science-based Ijtihad: religious and scientific dialectic on fatwas regarding congregational worships amid the covid-19 pandemic - Ali Sodiqin (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
The covid-19 pandemic has impacted religious practices, including Islamic practices. Islamic scholars have issued several fatwas which regulate how congregational worships should be practiced. For instance, a fatwa regulates that a worship which is supposed to be performed at a mosque collectively should be performed at home individually. The rapid spread of coronavirus becomes the primary reason for issuing this regulation. This study is a normative study which employs an usul fikih approach. The object of the study is the religious and scientific dialectic on fatwas regarding congregational worships amid the covid-19 pandemic. Data is collected by gathering fatwas issued by ulama councils around the world. The data is analyzed through a ta’lîly logic, that is a logical reasoning that is based on ‘illah (reason). This study is built upon the theory of istihsan bil maslahah, which refers to a theory about how Islamic laws can change depending on their benefits. This study presents three main findings. First, in issuing fatwas regarding the covid-19, ulama used scientific findings about the danger of coronavirus as ‘illah for changing the practice of congregational worships and employed as a lens to consider the benefit of a law. These ulama used the interrelationship model of interests (maslahah) in which preserving of soul (hifẓ an-nafs) was more important that preserving of faith (hifẓ ad-dîn). Second, the ulama methodologically combined religious method, which was based on interpretative approach, and scientific method, which was based on empirical approach. This integration of religious and scientific methods reflected doctrinal-philosophical aspect and legal-ethic aspect of the fatwas. Third, the fatwas indicated the use of functional interpretative approach towards scriptural texts, logic, and reality.